Notes on the Determinants of Innovation: A Multi-Perspective Analysis - Francesco Crespi (Fondazione Eni Enrico Mattei (FEEM), 2004)
The study of innovation and technological change is an increasing field of economic enquire because innovation can be considered a major engine of growth. This paper is concerned with the determinants of innovation and technological change. Different theoretical approaches present in the literature are systematically considered. The aim of this work is to offer an overview of contributions emerging from different perspectives trying to place them in their proper theoretical framework. The paper will be divided in different subsections in which each determinant is individually treated through the presentation of the most relevant results achieved by the literature on the specific issue. Policy considerations and hints for further research are also provided.
Keywords: O31; O33; O34; O38; 330; Determinants of innovation; Innovation and knowledge; National systems of innovation; Intellectual property rights; Technology policy; Innovation; Technischer Fortschritt; Humankapital; Immaterialgüterrechte; Technologiepolitik